The Principle of Protecting the Best Interests of the Child in Vietnamese Divorce Law - Huỳnh Thị Trúc, Giang (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
Divorce can have adverse effects on children in many ways, which has been extensively studied and demonstrated in scientific literature worldwide. Therefore, policymakers around the world, including Vietnam, have incorporated the principle of protecting the best interests of the child into their approach to addressing issues related to children during the process of their parents' divorce. This incorporation aims to reduce the negative impact of divorce on children and create a favorable environment for their comprehensive development. This article approaches the subject from the perspective of children's rights. Its objective is to introduce the application of the principle of safeguarding the best interests of children in the enactment and enforcement of divorce laws in Vietnam. It focuses on aspects such as determining the custodial parent, child visitation, child support, and changing the custodial parent